Pengaruh Kompetensi dan Kualitas Pelayanan Terhadap Kinerja Pelaku Ekowisata Kampung Kopi Mekarbuana-Karawang - Nandang Nandang; Wanta Wanta; Asep Jamaludin (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The purpose of this study was to determine the effect of competence and service quality on the performance of ecotourism actors in Kampung Kopi Mekarbuana,- Karawang. The method in this study uses a quantitative approach with path analysis. The source of this research uses primary data. Collecting research data using a questionnaire. The sample of this research is 35 respondents using random sampling technique. The results of hypothesis testing show that both simultaneously and partially there is a significant influence between competence and service quality on the performance of ecotourism actors in Kampung Kopi Mekarbuana – Karawang. There is a moderate positive and significant relationship between competence and Service Quality of Kampung Kopi ecotourism actors. The direct effect value of the competency variable on the performance of ecotourism actors is 0.159 and the indirect effect is 0.073. So that the total value of influence is 0.232. The direct effect value of the Service Quality variable on the performance of ecotourism actors is 0.186 and the indirect effect is 0.073. So that the total value of influence is 0.259. The total effect value of the Competency and Service Quality variables is 0.491 indicating that simultaneously the Competency and Service Quality variables affect the performance of ecotourism actors by 49.1% so that the remaining 50.09% is influenced by other variables not measured in the study.